EFEKTIFITAS BACA TULIS AL-QUR’AN DALAM MENINGKATKAN MINAT BACA AL-QUR’AN PADA ANAK USIA DINI: (STUDI KASUS DI TPA DAARUL ULUM DESA SAUSU KAB PARIGI MOUTONG) - Syafii, Ahmad (Pusat Studi Gender dan Anak, IAIN Palu, 2024)
The purpose of this study is to determine the application and effectiveness of reading and writing the Qur'an in increasing interest in reading the Qur'an in Early Childhood at the Daarul Ulum Landfill, Sausu Village, Parigi Moutong Regency. This research is a descriptive research with a qualitative approach. The subject of this study is teachers. Data collection was carried out using observation, interview, and documentation methods and analyzed using data reduction, data presentation, and conclusion drawn. The results of the study show that first, the application of reading and writing the Qur'an at the Daarul Ulum Landfill, Sausu Village, Parigi Moutong Regency by using several methods, namely the sorogan method, the weton method (halaqah) and the method of giving assignments or exercises. Second, reading and writing the Qur'an is effective in increasing interest in reading the Qur'an in Early Childhood at the Daarul Ulum Landfill, Sausu Village, Parigi Moutong Regency.. The implication shows a good thing, where the reading and writing of the Qur'an makes children from an early age understand the Qur'an correctly both in tajweed, pronunciation and writing in order to create quality children, who love the Qur'an.